Benchmarking the Financial Efficiency of Public Corporations in Mexico - Ablanedo-Rosas, Jose Humberto; Cutcher, Allen J.; Garcia, Michael S.; Conwell, William (International Journal of Economics and Financial Issues, 2025)
This research introduces a non-parametric approach, based on financial ratios, to assess the financial performance of public organizations. The approach utilizes financial ratios as outputs in an output-only Data Envelopment Analysis (DEA) model. The output-oriented DEA method estimates relative financial efficiency scores that are used to estimate efficiency densities via a kernel distribution with a normal optimal smoothing parameter. A kernel test of hypothesis is then used to perform financial performance comparisons between companies to assess the statistical significance of their performance differences. The proposed approach is tested when evaluating the financial efficiency of eight public Mexican corporations from 2018 to 2023. Hence, multiple heterogeneous financial ratios are combined into a single measure of efficiency, which allows ranking of the corporations’ performance based on their financial ratios. Results confirm the usefulness of the proposed approach and provide valuable data-driven insights for decision makers.